A Educação Ambiental no “Novo Ensino Médio”: uma análise nos livros didáticos da área de Ciências da Natureza e suas Tecnologias - Henrique Ferreira, Mateus (2023)
Environmental Education is an emerging field of knowledge that needs constant debate. Likewise, the New Secondary School, supported by the National Common Curricular Base, brings with it provocations about the meanings attributed to Environmental Education, requiring studies and investigations. With that in mind, the present study analyzed how textbooks in the Area of Natural Sciences and its Technologies in High School, approved by the National Textbook Program 2021, address Environmental Education, in the face of socio-environmental challenges. As a methodology adopted, documentary research was carried out, of a descriptive nature, based on Content Analysis, with the creation of three categories, namely: Conservationist Approach, Pragmatic Approach and Critical Approach, which refer to the political-pedagogical macrotrends. As a result, there was a discrepancy regarding the number of occurrences between the approaches, specifically with low occurrence in the Critical Approach and a predominance of the Pragmatic aspect, implying (in)directly in the critical formation of society.